POTRET PERTUMBUHAN EKONOMI, KESENJANGAN DAN KEMISKINAN DI INDONESIA DALAM TINJAUAN EKONOMI POLITIK PEMBANGUNAN - Hilmi Rahman (Jurnal Ilmu dan Budaya, 2017)
Of several arguments explaining about the success of economic development   of a country is the high rate of growth. Claims are made that indicative of prospect for such growth is the development of infrastructure. And the “philosophy” of economic development is the call for foreign investment and foreign debts to be invited to the country. What is missing is, instead, the hidden economic disparity that is potential in putting infrastructure development top priority. Unless control over the high rate is made effective, the high rate of growth would correlate with economic disparity whereby the regime in power would undergo more risks and in the long run would deteriorate political legitimacy.    Indonesia’s gini ratio index in the last three years has been at 0.42 indicating strong alarm of danger. Unless improvement is made Indonesia is likely to encounter social chaos. The paper is an account of the issue in the perspective of political economy.